Efektivitas Waktu Aplikasi Trichokompos dan Larutan Daun Sirih dalam Menekan Kejadian Penyakit Layu Fusarium pada Tanaman Padi Beras Merah (Oryza nivara L.) - Setiawan, Mario Yudi; Budi, Ismed Setya; Marsuni, Yusriadi (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Red rice (Oryza nivara L.) is a type of rice whose consumption level is increasing every year. However, obstacles in cultivating red rice often occur due to disease attacks, one of which is fusarium wilt. The aim of this research was to determine the effectiveness of varying the application time of trichocompost combined with betel leaf solution in suppressing the incidence of fusarium wilt disease in red rice plants. The research method used a Completely Randomized Design (CRD) which was carried out in the Phytopathology laboratory and greenhouse of the Department of Plant Pests and Diseases, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The results of the study showed that the treatment given trichocompost and betel leaf solution with application times a week before planting, during planting, and a week after planting was able to reduce the incidence of disease by up to 35.00% with a control effectiveness percentage of 62.16% compared to the control treatment which had the incidence disease amounted to 92.50%. Application of trichocompost and betel leaf solution with varying times on red rice was able to extend the incubation period of the pathogen up to 20.25 days compared to the control, namely 12.53 days. Plants that were given the application of trichocompost and betel leaf solution were also able to increase plant height by up to 102.83 cm with a total of 8.78 tillers compared to the control without treatment which had a plant height of 76.30 cm with a total of 4.30 tillers.